THE EFFECT OF CATECHINS FROM PURIFIED GAMBIER (UNCARIA GAMBIR ROXB.) AND VITAMIN C ON MALONDIALDEHYDE (MDA) LEVELS OF MALE WHITE MICE AFTER PHYSICAL ACTIVITY - YOSMAR, RAHMI; PUTRI, AYU AMELIA; A., ALMAHDY (International Journal of Applied Pharmaceutics, 2024)
Objective: The aim of this study was to assess the impact of catechins from purified gambier and vitamin C on the MDA levels of male white mice following maximum physical activity. Methods: This research employed an experimental approach using a Post Test Only Control Group Design with male white mice. The interventions included purified gambir catechin and vitamin C alongside physical fatigue-inducing activity. The primary focus was assessing serum MDA levels in these mice, measured using the Thiobarbituric Acid Reactive Substance (TBARS) method. The test subjects were divided into five groups and average serum MDA levels were measured in each group, followed by an analysis checking for normal distribution and homogeneity. Subsequently, One Way Analysis of Variance (ANOVA) was conducted. If significant differences were observed among the groups, further analyses were performed with a significance level of p<0.05. All tests maintained a confidence level of 95% (α = 0.05). Results: The average serum MDA values for the treated groups were 1.63 nmol/ml for the negative control, 2.47 nmol/ml for the positive control, 1.75 nmol/ml for purified gambier catechin 200 mg/kgBW, 1.93 nmol/ml for Vitamin C 65 mg/kgBW, and 1.65 nmol/ml for purified gambier catechin 100 mg/kgBW and vitamin C 32.5 mg/kgBW. Based on the Kruskal-Wallis test analysis, there was a significant difference in serum MDA levels (p<0.05) with a significance value of 0.004 of each group. However, the Mann-Whitney test showed that the negative control group significantly differed from the positive control group and there was a significant difference between the positive control and the treatment groups. Conclusion: The administration of catechins from purified gambier and vitamin C reduced MDA levels following maximum physical activity. Further study is recommended to investigate the efficacy of various antioxidants and their combinations in reducing MDA levels.